2021
DOI: 10.3390/molecules26113412
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Compositions, and Antibacterial and Antioxidant Activities of Four Types of Citrus Essential Oils

Abstract: Nanfeng mandarins (Citrus reticulata Blanco cv. Kinokuni), Xunwu mandarins (Citrus reticulata Blanco), Yangshuo kumquats (Citrus japonica Thunb) and physiologically dropped navel oranges (Citrus sinensis Osbeck cv. Newhall) were used as materials to extract peel essential oils (EOs) via hydrodistillation. The chemical composition, and antibacterial and antioxidant activities of the EOs were investigated. GC-MS analysis showed that monoterpene hydrocarbons were the major components and limonene was the predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 40 publications
6
35
1
1
Order By: Relevance
“…Results revealed that all the NL and PO EO analyzed showed antioxidant activity (Figure 4). This result is in accordance with other antioxidant studies of several Citrus EO, such as C. aurantium [40,41], C. aurantifolia [41], C. reticulata [8,40], C. sinensis [40], C. limon [40], C. lumia [42], and other Citrus species [43][44][45]. In our study, the values of antioxidant activity ranged from 5.03% ± 3.76 to 39.43% ± 5.39 for NL, and from 12.10% ± 4.99 to 31.54% ± 3.04 for PO, including all dates of the two seasons.…”
Section: Antioxidant Activity Of Nl and Po Eosupporting
confidence: 92%
“…Results revealed that all the NL and PO EO analyzed showed antioxidant activity (Figure 4). This result is in accordance with other antioxidant studies of several Citrus EO, such as C. aurantium [40,41], C. aurantifolia [41], C. reticulata [8,40], C. sinensis [40], C. limon [40], C. lumia [42], and other Citrus species [43][44][45]. In our study, the values of antioxidant activity ranged from 5.03% ± 3.76 to 39.43% ± 5.39 for NL, and from 12.10% ± 4.99 to 31.54% ± 3.04 for PO, including all dates of the two seasons.…”
Section: Antioxidant Activity Of Nl and Po Eosupporting
confidence: 92%
“…This result corresponds to higher values reported in the study of Almeida et al [38], who examined seven accessions of sour orange from Brazil. This disparity could be explained by environmental and/or genetic factors, particularly for this species, which presents glandular trichomes on the surface of the leaves [25,[38][39][40][41].…”
Section: Essential Oil Yield and Compositionmentioning
confidence: 98%
“…The temperature of the injector was maintained at 250 • C and that of the detector at 270 • C. As to the temperature of the column, the following sequence was performed: an initial temperature of 50 • C was maintained for one minute, then raised from 50 to 175 • C at a rate of 5 • C per minute. The temperature of 175 • C was maintained for 10 min, then raised from 175 to 250 • C in one step at a rate of 15 • C per minute [25].…”
Section: Chemical Characterization Of Eo By Coupling Gas Chromatograp...mentioning
confidence: 99%
“…Citrus sinensis In this study 2006 [28] 2009 [29] 2012 [30] 2017 [17] 2017 [31] 2019 [32] 2020 [15] 2020 [14] 2020 [33] 2020 [34] 2020 [35] 2021 [36] Vietnam Citrus aurantium In this study 2016 [37] 2018 [18] 2019 [5] 2019 [38] 2021 […”
Section: Table 2 Comparison Of Compounds In Orange Essential Oil (Cit...mentioning
confidence: 99%